Usefulness of Red Cell Distribution Width to Predict Mortality in Patients With Peripheral Artery Disease - Ye, Zi; Smith, Carin; Kullo, Iftikhar J. (The American journal of cardiology, 2011)
Increased red blood cell distribution width (RDW), a marker of anisocytosis, has been associated with adverse outcomes in multiple settings. Whether RDW is predictive of mortality in patients with peripheral artery disease (PAD) is unknown. We studied 13,039 consecutive outpatients (69.5 ± 12.0 years of age, 60.9% men, 97.6% white) with PAD identified by noninvasive lower-extremity arterial testing at the Mayo Clinic from January 1997 through December 2007, with follow-up through September 2009. We defined PAD as a low (≤0.9) or high (≥1.4) ankle–brachial index (ABI). Cardiovascular risk factors and co-morbidities were ascertained using electronic medical record–based algorithms. RDW was obtained from the complete blood cell count drawn around the time of arterial evaluation. Mortality was ascertained using the Mayo electronic medical record and Accurint databases. Association of RDW with all-cause mortality was analyzed by multivariable Cox proportional hazards regression. During a median follow-up of 5.5 years, 4,039 (31.0%) deaths occurred (28.7% in low and 38.9% in high ABI subsets). After adjustment for age, gender, cardiovascular risk factors, and co-morbidities, patients in the highest quartile of RDW (>14.5%) had a 66% greater risk of mortality compared to the lowest quartile (<12.8%, p <0.0001); a 1% increment in RDW was associated with a 10% greater risk of all-cause mortality (hazard ratio 1.10, 95% confidence interval 1.08 to 1.12, p <0.0001). The adjusted hazard ratio was similar in the low (1.10, 1.08 to 1.12) and high (1.09, 1.06 to 1.12) ABI subsets. In conclusion, RDW, a routinely available measurement, is an independent prognostic marker in patients with PAD.